Dispersion behaviour and agglomeration effects of zinc oxide nanoparticles in ethanol-water mixtures - Ilyas, S.U. (Maney Publishing, 2014)
Nanofluids are the new engineered fluids with particles of nanometre size as an additive to alter the effective thermal and viscous properties for different applications. Settling of nanoparticles because of agglomeration among particles in the liquid is a big challenge towards the stability of nanofluids. The dispersion behaviour of nanofluids using zinc oxide nanoparticles of 30 and 40 nm size in ethanol-water mixtures has been examined. Sediment heights are measured at different time intervals with and without ultrasonication using conventional batch sedimentation apparatus. The effect of different nanoparticle concentrations in variety of ethanol-water proportions has been studied using the photographic method. Agglomeration effect has been studied with and without sonication in terms of sedimentation ratio and with the support of transmission electron microscopy. It is found that sonication has a significant influence on the nanofluid stability. An important evaluation technique for stability of nanofluids has been presented. Â© 2014 W. S. Maney & Son Ltd.